Antibacterial Activities of Guava Leaves and Klutuk Banana by In Vitro as Antidiarrhea - Ira Rahmiyani; Anna Yuliana; Mitha Anggitha; Vera Nurviana (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Klutuk banana fruit and red shoots of guava leave added with salt used by Batra in Jayaratu SingaparnaVillage to treat diarrhea. The green shoots of guava used by the community in treating diarrhea thanklutuk bananas. This study aims to compare the activity of klutuk banana flesh (K) and red shoots ofguava leaves (M) with the addition of salt (G), which Batra commonly uses with green shoots of guavaleaves (H) used by the general public and their combinations to inhibiting Escherichia coli bacteria.This study was conducted in vitro with Simplicia test samples of guava leaf shoots and banana klutukcharacterized. Each sample was crushed, and the extract was taken and tested for antibacterial activity.Data analysis used One Way Analysis of Variant (Anova) and continued with the Least SignificantDifference (LSD) test. The results showed that samples M, H, K, HG, MHG, and MH providedresistance to E. coli ATCC 25922 with a significance value of 0.000 (p<0.05), whereas the HG and Hgroups did not show a significant difference (P >0.05). The red and green shoots of guava leaves, singlyor in combination have potent antibacterial activity. The variety of red shoots and green leaves of guavawith a mixture of salt (MHG) concentration of 100% (1:1:1) had the highest MIC value compared tothe other groups.